Studi Numerik Model Virus Hepatitis B dengan Pengaruh Penyembuhan dan Absorpsi - Lisa Risfana Sari; Puji Andayani (Universitas PGRI Palembang, 2019)
The phenomenon of Hepatitis B outbreak almost occurs in all developing countries including Indonesia. Hepatitis B infection can develop into acute or chronic. In the chronic stage, the infection can cause liver complications such as liver cirrhosis or liver cancer or even death. Mathematical modeling have been widely used to study the Hepatitis B virus infection. In this study a mathematical model is constructed by considering non-cytolytic immune response and pathogen absorption. The model is analyzed by determining the equilibrium point of the model, determining the existence of the equilibrium point, and analyzing the stability of the equilibrium point of the model with numerical simulation. In this case, numerical analysis is used to illustrate the conditions of infection-free and infected. Furthermore, the relation of the stability requirements of each equilibrium point is studied. The results show that there are two equilibrium points, uninfected and infected equilibrium point. Both of the uninfected equilibrium point and infected equilibrium point is asymptotically stable if a certain condition are met. Based on these results, the causes of a persistent infection are studied.